To-day's the day (draft leaflet)
028-0014-001 August 1936 TO-DAY'S THE DAY. The Fund is nearing £5,000 and it is hoped that, in connection with the request of the National Council of Labour, arrangements are now being made for factory and workshop collections to-night, Friday, and to-morrow, Saturday. There is no general issue of collecting sheets it being anticipated that organisations will be making their own arrangements in regard to the collections which should only be taken through duly authorised collectors. An official receipt is issued in respect of every amount sent in and Branch Secretaries and others responsible for shop collections will receive one of these official receipts. Do your bit to make this week-end one of material assistance to those in Spain fighting for constitutional government and democracy. 292/946/28/14